Centenarians as a model for healthy aging. (1st April 2003) - Franceschi, C.; Bonafè, M.
Abstract : For over 10 years we have studied centenarians as a model to address the biological basis of aging and longevity, with particular attention to immunology and genetics. The most important findings can be summarized as follows. (i) Human immunosenescence represents a complex remodelling, whereby clonotypical immunity deteriorates, while ancestral, innate immunity is largely preserved. (ii) Continuous exposure to antigens causes a lifelong, chronic antigenic stress, which is responsible, together with the involution of the thymus, for the accumulation of memory/effector T cells and the exhaustion of naïve T cells. (iii) Aging is characterized by a peculiar chronic inflammatory status that we propose to call 'inflammaging', which appears to be under genetic control, is detrimental for longevity and is more evident in men than in women. Inflammaging, i.e. the up-regulation of a variety of anti-stress responses at the cellular and molecular level, is the consequence of the ability of the body to adapt to and counteract the effects of a variety of stressors, which causes the accumulation of molecular and cellular scars. Inflammaging is considered the common and most important driving force of age-related pathologies, such as neurodegeneration, atherosclerosis, diabetes and sarcopenia, among others, all of which share an inflammatory pathogenesis. (iv) Possible strategies to counteract the major effects of immunosenescence and inflammaging, such as the systematic reduction of the lifelong antigenic load, the elimination of chronic infections, thymic rejuvenation and preventative treatment with anti-inflammatory drugs in people with a pro-inflammatory genotype, are envisaged.